A dinâmica da organização interna da mesa diretoria e comissões da assembléia do estado do Rio de Janeiro - Araújo, Monica Maria Martins de (2003)
The globalization of the capitalism throws the individual in world fxxll of controversy, almost an existential crisis, once it reels between the dream to satisfy ali one's desire and the reality which may not accomplish. What interests to the globalization is the emotional hangover from the individual, what makes him distant from his reason, from the balance between the power and the willing and turn him into compelling of expenditure. It is the mass-produced and cultural homogenization process. that not only beget consumptive addiction on the individual, as obstruct him to take part politically, too. Politically, one of the globalization first step is featured by the aegis from the absolutist monarchy that concentrates huge power and mobilize the economic resources, military and bureaucratic, to maintain and enlarge their colonial empire. The main challenger that they faced, have come from the rivalry among them, being by the dynastical territorial disputes or by taking office of new colonies from overseas. Politically the recent period in globalization is distinguished by the increasing adoption of political systems that are looking for wider and shared democracy to the political participation, in so far as, is basic demanding to the individual to overcome the barriers that are inflicted by the globalization and achieve to develop citizenhood actions within the global society itself. In this sense, it is necessary to shorten the distance among the existent institutional kinds, whatever they are, juridical or political, and the real possibility to recognize on the Law and in the institutions their own Law and their own power.